2020
DOI: 10.3390/brainsci10090621
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Interhemispheric Coherence after Cerebellar Vermis Output Perturbation

Abstract: Motor coordination and motor learning are well-known roles of the cerebellum. Recent evidence also supports the contribution of the cerebellum to the oscillatory activity of brain networks involved in a wide range of disorders. Kainate, a potent analog of the excitatory neurotransmitter glutamate, can be used to induce dystonia, a neurological movement disorder syndrome consisting of sustained or repetitive involuntary muscle contractions, when applied on the surface of the cerebellum. This research aims to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“… 35 Thus, independent of surgery type, vulnerability of the cerebellum to perioperative infarction and the associated risk for subsequent delirium appears to be high. The pathophysiological mechanisms of this association are still relatively obscured, but the role of the cerebellum in brain network oscillatory activity via the cortico‐thalamo‐cerebellar pathway is one hypothesis, as dysfunction in this circuit can have a negative impact on interhemispheric communication and has been suggested as the basis for “dysmetria of thought.” 36 , 37 , 38 Non‐motor deficits arising from lesions damaging the cortico‐cerebellar connection, such as the cognitive abnormalities seen in patients with cerebellar cognitive affective syndrome (aka. Schmahmann's syndrome) 39 are routinely observed during delirium states (e.g., executive dysfunction, affective dysregulation, attention, and working memory impairment).…”
Section: Discussionmentioning
confidence: 99%
“… 35 Thus, independent of surgery type, vulnerability of the cerebellum to perioperative infarction and the associated risk for subsequent delirium appears to be high. The pathophysiological mechanisms of this association are still relatively obscured, but the role of the cerebellum in brain network oscillatory activity via the cortico‐thalamo‐cerebellar pathway is one hypothesis, as dysfunction in this circuit can have a negative impact on interhemispheric communication and has been suggested as the basis for “dysmetria of thought.” 36 , 37 , 38 Non‐motor deficits arising from lesions damaging the cortico‐cerebellar connection, such as the cognitive abnormalities seen in patients with cerebellar cognitive affective syndrome (aka. Schmahmann's syndrome) 39 are routinely observed during delirium states (e.g., executive dysfunction, affective dysregulation, attention, and working memory impairment).…”
Section: Discussionmentioning
confidence: 99%
“…Fremont et al identified that in mice with ouabain-induced lesions the presence of dystonia was accompanied by persistent high-frequency bursts of cerebellar nuclear neurons, and restoration of the ouabain-blocked sodium channels alleviated the symptoms of dystonia as assessed with rotarod and observation assays [ 152 ]. Georgescu Margarint et al created an electromyographical setup that showed lateralized or vermal cerebellar dysfunction (due to kainic acid administration) ultimately triggered dystonia that was associated with a loss of connectivity in the corresponding cortical motor cortices ( Figure 3 ) [ 153 , 154 ], mirroring the human imaging studies in dystonic CP and task specific dystonias. Such studies have highlighted the evolutionary conservation of the dystonia network and shown that anatomic and circuit derived manipulations of the network can inform and confirm findings in the clinical population.…”
Section: Rodent Models Of Functional and Acquired Dystoniamentioning
confidence: 99%
“…Therapeutic modulation of the cerebellum or its outflow pathway was occasionally found to be effective in the treatment of dystonia (19,20). In animal models, dystonia can be triggered by kainic acid (a glutamate receptor agonist) injection into the cerebellum surface (21)(22)(23). Raike et al showed that focal and generalized dystonia may have similar physiopathology and can be treated with similar strategies (24).…”
Section: Introductionmentioning
confidence: 99%